Postpartum evaluation of cardiovascular disease risk for women with pregnancies complicated by hypertension - Escouto, Daniele Cristovao; Green, Amanda; Kurlak, Lesia; Walker, Kate; Loughna, Pamela; Chappell, Lucy; Broughton Pipkin, Fiona; Bramham, Kate (Elsevier, 2018)
Objectives: Postpartum stratification of cardiovascular risk for women with pregnancies complicated by pre-eclampsia is challenging. Our aim was to identify potential clinical and biomarker predictors of future cardiovascular risk at six weeks postpartum in women with hypertensive pregnancies. Study design: Prospective longitudinal cohort. Main outcome measures: Ten year-Framingham cardiovascular risk scores were calculated for 477 women (94 with gestational hypertension, 288 with pre-eclampsia, 30 with superimposed pre-eclampsia, 51 with chronic hypertension, 14 women with uncomplicated pregnancies). B-type natriuretic peptide (BNP), neutrophil gelatinase–associated lipocalin (NGAL) and placental growth factor (PlGF) were quantified at six weeks postpartum. Results: Framingham cardiovascular risk scores were not higher in women with pregnancies complicated by pre-eclampsia than healthy controls, nor were scores higher in women with pre-existing chronic hypertension complicated with superimposed pre-eclampsia compared with those without superimposed pre-eclampsia. Women with gestational hypertension had higher risk scores than women with pre-eclampsia and healthy controls. Established risk factors of cardiovascular disease including diastolic blood pressure and previously diagnosed chronic hypertension were associated with higher scores, and African ethnicity, parity and estimated glomerular filtration rate also were independently associated with higher Framingham risk scores at six weeks postpartum. PlGF, BNP and NGAL concentrations were not associated with Framingham cardiovascular risk scores after adjustment for independent variables. Conclusions: A history of pre-eclampsia or superimposed pre-eclampsia in most recent pregnancy was not associated with elevated Framingham risk score at six weeks postpartum. Established clinical predictors may enable risk stratification at six weeks postpartum, which are not enhanced by the biomarkers included in this study.